Empowerment and Welfare of Bakaran Batu Village Families in Making Empon Menieer Mixture as Body Immunity to Improve the Community's Economy: Pemberdayaan dan Kesejahteraan Keluarga Desa Bakaran Batu Dalam Pembuatan Racikan Empon Menieer Sebagai Imunitas Tubuh Untuk Meningkatkan Perekonomian Masyarakat - Shufyani, Fahma; Fitri, Khairani; Manaharawan Siregar, Syati (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Community service aims to increase economic income from Empon Menieer concoctions as health products, acquire new skills with high economic value in the market, and improve family welfare by developing additional businesses that can enhance body immunity. The benefits of Empon Menieer and its processing methods, along with skills in entrepreneurship and small business management, can be enhanced through training and mentoring. Herbal and traditional medicine practices, passed down through generations, are part of the parents' responsibility to preserve customs and traditions. The method involves preparing activities through coordination in the initial meeting, obtaining permission and support from the Head of the PKK (Family Welfare Movement), forming a team consisting of students, lecturers, and village community representatives, collecting materials for making Empon Menieer concoctions, and preparing visual aids for socialization. The community participants are divided into 3 groups, each consisting of 10 people, totaling 30 people for direct practice in making Empon Menieer with guidance from lecturers and students. The results of making the Empon Menieer concoctions can improve economic income as health products, provide new skills with high market value, and enhance family welfare by developing additional businesses that can boost immunity, thus maintaining the health of the village community. Participants also gain new knowledge about the benefits of Empon Menieer and its processing methods, and skills in entrepreneurship and small business management are improved through training and mentoring. The conclusions of the progress of the Community Service Program (PKM) include: the village PKK actively participates in forming the village PKK groups during the mentoring process of making Empon Menieer concoctions, enhancing the knowledge of the Bakaran Batu village community and students after attending the training.